As raízes antiliberais de Sérgio Buarque de Holanda: Carl Schmitt em Raízes do Brasil - Douglas Carvalho Ribeiro (2017)
The present work aims to investigate the various appropriations of Carl Schmitt's theory by Sérgio Buarque de Holanda in the conception of the radically different projects to which the 1936 and 1948 editions of Raízes do Brasil refer. The starting point is a panoramic approach of Carl Schmitt's theory, highlighting the author's antiliberalism as a constant in his work. Then the focus will reside in the writings of the Young Sérgio Buarque de Holanda, seeking the possible points of contact between the theories of Holanda and Schmitt. Afterwards, the many appropriations of Schmitts theory by Holanda concerning the first edition of Raízes do Brasil will be investigated, especially the conceptual elaboration of cordiality as subjectified occasionalism and the defense of the charismatic form of domination. Subsequently the analysis is oriented to the modifications made in the second edition of Raízes do Brasil, which conferred the Schmittian theory a new function within the narrative, especially related to a Theory of the Public. Finally, it will be proposed a reconstructive reading of the 1936 edition of that book, in order to establish a critical position regarding the new forms of relation between State and society, guided mainly by the notion of governance and the realization of the so-called new public management.